Historical blocking: IR 2022-09-13 to 2023-01-18 (Iran) - Voidly (Voidly Global Censorship Index, 2022)
CRITICAL severity censorship detected in Iran. Data sourced from ooni-historical-backfill.
Censorship Incident ID: IR-2022-0511. Severity: critical. Confidence: 98%